2022
DOI: 10.1002/acn3.51543
|View full text |Cite
|
Sign up to set email alerts
|

Genetic spectrum in a cohort of patients with distal hereditary motor neuropathy

Abstract: Background Distal hereditary motor neuropathy (dHMN) is a heterogeneous group of diseases characterized by exclusive degeneration of peripheral motor nerves, while only 20.0–47.8% of dHMN patients are genetically identified. Recently, GGC expansion in the 5’UTR of NOTCH2NLC has been associated with dHMN. Accordingly, short tandem repeat (STR) should be further explored in genetically unsolved patients with dHMN. Methods A total of 128 patients from 90 unrelated families were clinically diagnosed as dHMN, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…More recently, the expansion accounted for 10.6% (seven of 66) of molecularly unsolved CMT2 cases in a Taiwanese Charcot–Marie–Tooth disease (CMT) cohort, and most affected individuals presented as mild axonal sensorimotor polyneuropathy [16]. In addition, distal hereditary motor neuropathy was identified in some patients with CGG expansion in NOTCH2NLC [17]. Collectively, pure or dominant peripheral neuropathy mimicking CMT can be one phenotype of NIID.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the expansion accounted for 10.6% (seven of 66) of molecularly unsolved CMT2 cases in a Taiwanese Charcot–Marie–Tooth disease (CMT) cohort, and most affected individuals presented as mild axonal sensorimotor polyneuropathy [16]. In addition, distal hereditary motor neuropathy was identified in some patients with CGG expansion in NOTCH2NLC [17]. Collectively, pure or dominant peripheral neuropathy mimicking CMT can be one phenotype of NIID.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it was necessary to measure the CGG repeat number to determine its pathogenicity in the genetic diagnosis of NIID patients. The repeat expansion in NOTCH2NLC also showed some rare clinical phenotypes, such as neurodegenerative dementia ( Jiao et al, 2020 ), non-vascular leukoencephalopathy ( Liu et al, 2022 ), motor neuron disease ( Yuan et al, 2020 ), sensorimotor with autonomic neuropathy ( Wang et al, 2021 ), distal motor neuropathy ( Wu et al, 2022 ), as well as oculopharyngeal distal myopathy (OPDM) ( Yu et al, 2021 ). Because of the small number of these cases, the relationship between the clinical phenotype and the number of CGG repeat had not been established, but distal motor neuropathy and OPDM were generally considered to have more repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies have indicated that carriers with more than 300 repeats of expanded CGG show a mild or asymptomatic phenotype [ 20 , 127 ]. Beyond NIID, expanded CGG repeats in NOTCH2NLC are occasionally related to a small proportion of Parkinson's disease (PD) [ 65 , 97 , 110 ], multiple system atrophy (MSA) [ 29 ], essential tremor (ET) [ 105 ], degenerative dementia [ 4 , 101 ], ALS [ 46 , 130 ], inherited peripheral neuropathy [ 118 ], distal motor neuropathy [ 122 , 128 ], mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) [ 57 , 123 ], and oculopharyngodistal myopathy (OPDM) [ 127 ]. Intriguingly, CGG expansion in NOTCH2NLC was rarely detected in NIID cases reported in people of Caucasian descent, suggesting that NIID is likely to be genetically heterogeneous among different ethnic groups [ 15 ].…”
Section: Polyglycine(g) Disordersmentioning
confidence: 99%